PENGARUH PROFITABILITAS, LEVERAGE DAN INCOME SMOOTHING TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2016-2018 - Owa, Ermelinda; Purwanto, Nanang; Sari, Ati Retna (Jurnal Riset Mahasiswa Akuntansi, 2019)
Company value is investors' perception of the level of success of a company. The level of success of a company is usually often associated with stock prices. High stock prices make the value of the company also increased. In this study, sampling was conducted using a purposive sampling method. For the data analysis technique the researchers used multiple linear regression analysis techniques. From the results of hypothesis testing that has been done, it shows that profitability, leverage and income smoothing simultaneously affect the value of the company. When viewed commercially, the results of hypothesis testing profitability variables have an influence on firm value. Furthermore, the results of the analysis of leverage variables also have an influence on firm value variables. The fourth analysis shows that the income smoothing variable affects the value of the company. Based on research that has been done, it is suggested, for investors before investing can see the value of the company first as a consideration made before investing.